Rules of Origin and Non-Tariff Barriers in Agricultural Trade: Perspectives from Bangladesh and Cambodia - Uttam Kumar Deb (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2006)
Many developed and developing countries have been offering special schemes to benefit least developed countries (LDCs) from trade through increased market access. However, effective utilization of market access opportunities by the LDCs may be constrained by the rules of origin (RoO) criteria and non-tariff measures (NTMs) applied by the preference-giving countries. This report deals with RoO applied and non-tariff barriers (NTBs) imposed by developed and developing countries for importing agricultural products from LDCs.
Keywords: F1; 330; Rules of Origin; Non-Tariff Measures